Sebuah artikel BIAYA JANGKA PENDEK & EFISIENSI SYARIAH (Analisis pada toko Ummuza Brownies Bakar): Pendahuluan, Kerangka Teoretis dan Studi Empiris, Metode Penelitian, Hasil dan Pembahasan, Kesimpulan, Saran dan Keterbatasan, Ucapan Terima Kasih - Fella Fella Attaqy; Mahyarni Mahyarni; Tun Rustam; Muhamad Rahman Selvarian (Eqien - Jurnal Ekonomi dan Bisnis, 2026)
In the context of increasing competition and resource constraints faced by micro-enterprises, effective cost management and production efficiency have become crucial for business sustainability, particularly when aligned with Islamic economic principles. This study aims to analyze the short-term cost structure and the implementation of production efficiency based on Islamic economics at the Ummuza Brownies Bakar Store as a micro-enterprise case. The research employs a descriptive qualitative approach, with data collected through in-depth interviews with the owner and employees, participatory observation of operational activities, and document analysis of financial reports and cost records. Data were analyzed thematically to identify fixed and variable cost management practices as well as efficiency strategies applied in the production process. The findings reveal that short-term costs consist of fixed costs, including cashier application subscriptions, employee wages, and transportation expenses, as well as variable costs such as raw materials, packaging, energy consumption, and promotion costs. Cost management is conducted in a structured manner and adjusted to production volume to minimize inefficiencies and waste. The study concludes that production efficiency at Ummuza Brownies Bakar is not solely oriented toward cost optimization but also emphasizes compliance with Islamic values, including halal assurance, transparency, fairness, and the avoidance of riba and isrāf, indicating that sharia-based efficiency can serve as a sustainable strategy for enhancing both economic performance and ethical business practices in micro-enterprises.